2022
DOI: 10.3390/biology11040491
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Analysis of Plant Resources among Five Ethnic Groups in the Western Himalayan Region of Jammu and Kashmir

Abstract: Plant resources have always been valuable in human life, and many plant species are used in medicine, food, and ritual, and resource utilization is closely related to cultural diversity. Our study was conducted from June 2019 to April 2021, during which we aimed to document the local knowledge of plant resources of five ethnic groups, i.e., the Gujjar, Bakarwal, Kashmiri, Pahari, and Dogra communities of the Jammu and Kashmir (J&K) region, Western Himalayas. Through semi-structured interviews (N = 342) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…The P -values are displayed at the top, and Pearson correlation coefficients are displayed at the bottom ( Figure 11 ). Various ethno-veterinary ethnoveterinary studies, such as Majekodunmi et al ( 61 ) from West Africa, Catley ( 62 ) from East Africa, Raza et al ( 63 ) from Pakistan's Cholistan desert, Rezende et al ( 64 ) from Minas Gerais, and Haq et al ( 65 , 66 ) from the Himalayas, have shown similar hierarchical clustering, multidimensional scaling, and associations.…”
Section: Resultsmentioning
confidence: 92%
“…The P -values are displayed at the top, and Pearson correlation coefficients are displayed at the bottom ( Figure 11 ). Various ethno-veterinary ethnoveterinary studies, such as Majekodunmi et al ( 61 ) from West Africa, Catley ( 62 ) from East Africa, Raza et al ( 63 ) from Pakistan's Cholistan desert, Rezende et al ( 64 ) from Minas Gerais, and Haq et al ( 65 , 66 ) from the Himalayas, have shown similar hierarchical clustering, multidimensional scaling, and associations.…”
Section: Resultsmentioning
confidence: 92%
“…It is the home to many ethnic communities, such as Bakarwals (nomads, occupying the high-altitude regions of Kupwara), Kashmiri (living in the main valleys and are in majority) and Gujjars which are inhibited in the region form centuries. (Haq et al 2022).…”
Section: Study Areamentioning
confidence: 99%
“…Humans have been utilizing therapeutic plants since ancient times and there has been documentation of their uses for a long time (Singh et al 2020). Traditional medicine is considered as the total knowledge, human abilities and cultural practices of a community based on their beliefs, experience and theories, employed for the treatment or enhancement of both physical as well as mental health (WHO 2002;Haq et al, 2022). Developed countries often have better access to modern medicines, numerous cases allopathic medicines are derived from molecules of natural origin (plant or animal) .…”
Section: Introductionmentioning
confidence: 99%
“…The difference in use patterns might be due to cultural and biological differences as well as geographic separation of the regions (Gairola et al 2014;Haq et al 2022).…”
Section: Comparative Assessment With Previous Regional Studiesmentioning
confidence: 99%